The exchange of roles between the ego and the other in the poetry of IbnHariqAl-Balansi (Journal of the College of Basic Education, 2023)
The Valencian poets tended to establish a close relationship with the words of nature, using them in the manner of the previous poets of Andalusia, IbnHariq al-Balansi was one of the conservative poets, and like IbnHariq al-Balansi joined those who preceded him and those who followed him to this school, including IbnKhafaja and his nephew Ibn al-Zaqaq, and al-Rasafi al-Balansi, In addition to Ibn al-Abbar, IbnJubayr, and others, they were seduced by the enchanting atmosphere of nature, including the sky, sun, rivers, and Riyadh, In addition to the battles they are fighting, whether from near or far, the poet's eye was like a lens capturing every moment and a beautiful scene that raises astonishment in his imagination, so he works on translating, photographing and embodying it.